The price of inflation and foreign exchange risk in international equity markets - Cesare Robotti (Federal Reserve Bank of Atlanta, 2001)
In this paper the author formulates and tests an international intertemporal capital asset pricing model in the presence of deviations from purchasing power parity (II-CAPM [PPP]). He finds evidence in favor of at least mild segmentation of international equity markets in which only global market risk appears to be priced. When using the Hansen & Jagannathan (1991, 1997) variance bounds and distance measures as testing devices, the author finds that, while all international asset pricing models are formally rejected by the data, their pricing implications are substantially different. The superior performance of the II-CAPM (PPP) is mainly attributable to significant hedging against inflation risk.
Keywords: 330; Hedging (Finance); Asset pricing; Foreign exchange; Risk